Perumusan dan Penyelesaian Persamaan Kesetimbangan dalam Analisis Dinamis pada Bangunan Tinggi Berbasis Website - Hans Christian Herjanto; Justinus Andjarwirawan; Henry Novianus Palit (Jurnal Infra, 2015)
Applications commonly used to solve the equations of dynamic analysis produce output that is less accurate because the use of mass implementation is less precise. Most of the applications are commercial and require the installation process before they can be used. The authors developed an application that uses website as the user interface, so that it can be accessed easily and does not require any installation process. The Website was created by using a more precise mass implementation so that the output becomes more accurate with simulated deformation and structure deflection.The Authors designed the website so that a user can have an account to make a project that is public or private, and an admin can manage the member data. Input process data are entered into tables with tabs such as node, properties, elements, joint mass, joint loads, ground acceleration, process so that the user can perform data input easily. Dynamic analysis calculation is performed by processing the input data using the Newmark method involving the creation of stiffness, mass, damping matrices the initialization of displacement, velocity, and acceleration the calculation of integration constants, the creation of element stiffness matrix, the calculation of displacement with time dependent, the calculation of displacement, velocity and acceleration.This dynamic analysis website generates outputs like all mentioned matrices in each element,  structure stiffness matrix, structure mass matrix, and displacement vector that conform with the exact solution. Results of displacement vector are  used to display the simulation of deformation and structure deflection at each time interval so the the structurak changes are observable from the beginning to the end.